The Determining Factors of Generation Z Purchase Decision for the Local Brand T-Shirt - Sharon K.D Wardoyo; Ronny H. Walean (Jurnal Multidisiplin Madani, 2022)
The study aims to determine the determinants factors on T-shirt purchasing decision for the local brand.  The sampling technique used purposive sampling with a total of 310 respondents proportionally male and female each of 155 respondents.  Analysis data used exploratory factor analysis technique with Principal component analysis method. Regarding BEKRAF data of the creative economy that has not been spread evenly and supported by the number of Indonesians aged 15-24 years as the target consumers of local brand t-shirts, the objective of this study is to determine the determinant factors of generation Z purchase decision for local brand T-shirts.  This study found six determinant factors.  They are the trend, digital channel, social media influencer, brand originality, simplicity, and motif.  The trend factor has the highest eigenvalues. Independent T-test indicates a different perception between males and females in the decision to buy the local brand t-shirt